2022
DOI: 10.3390/horticulturae8030230
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Inducible Overexpression of SlDDF2 Gene Improves Tolerance against Multiple Abiotic Stresses in Tomato Plant

Abstract: Dehydration-responsive element-binding protein 1 (DREB1)/C-repeat binding factor (CBF) family plays a key role in plant tolerance against different abiotic stresses. In this study, an orthologous gene of the DWARF AND DELAYED FLOWERING (DDF) members in Arabidopsis, SlDDF2, was identified in tomato plants. The SlDDF2 gene expression was analyzed, and a clear induction in response to ABA treatment, cold, salinity, and drought stresses was observed. Furthermore, two transgenic lines (SlDDF2-IOE#6 and SlDDF2-IOE#9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
0
0
Order By: Relevance
“…Interestingly, this gene rendered plants highly insensitive to ABA and proposed to regulate abiotic stress tolerance possibly in an ABA-independent manner [53]. Similarly, tomato overexpression of the transgenic line of dwarf and delayed flowering 2 (SlDDF2) under stress-inducible RD29a promoter showed better growth performance and tolerance under abiotic stresses including salinity and drought [54]. Overall, these studies suggested that identification of the key gene inducible under multiple stresses, and its overexpression in plants, is an effective strategy for developing multi-stress resilient crops.…”
Section: Gain-of-function Approach Through Gene Overexpressionmentioning
confidence: 99%
“…Interestingly, this gene rendered plants highly insensitive to ABA and proposed to regulate abiotic stress tolerance possibly in an ABA-independent manner [53]. Similarly, tomato overexpression of the transgenic line of dwarf and delayed flowering 2 (SlDDF2) under stress-inducible RD29a promoter showed better growth performance and tolerance under abiotic stresses including salinity and drought [54]. Overall, these studies suggested that identification of the key gene inducible under multiple stresses, and its overexpression in plants, is an effective strategy for developing multi-stress resilient crops.…”
Section: Gain-of-function Approach Through Gene Overexpressionmentioning
confidence: 99%
“…Recently, some favorable genes were found to overcome multiple stress tolerances (salinity, drought, high temperature, and osmotic stress) in several species, such as Arabidopsis, beans, tomatoes, and wheat [25][26][27][28]. Although those genes offer crucial insights into multiple stress tolerance mechanisms, legal restrictions prevent these genetically modified plants from progressing beyond laboratory and/or greenhouse experiments [29].…”
Section: Introductionmentioning
confidence: 99%